POTENSI OBJEK WATU KAPAL SEBAGAI DESTINASI GEOWISATA DI DESA SRIMULYO, KECAMATAN PIYUNGAN, KABUPATEN BANTUL - Fandika Agustiyar; Hendry Wirandok; Rois Naimudin (Jurnal Pariwisata Indonesia, 2021)
Sitimulyo village has been known by the public with the tourist destination Watu Kapal. Watu Kapal object has an extraordinary attraction and potential to be developed into geotourism judging by the characteristics of geology, socio-cultural, educational values, conservation and creative economy of the community. This research aims to find out the potential of "Watu Kapal" as the development of geotourism objects. Methods used in the form of field surveys, qualitative and quantitative descriptions of research sites. The assessment was conducted with reference to Kubalikova (2013). The results of the study obtained a value of 63.5%, indicating that the object Watu Kapal has the potential to be developed into a geotourism object. In the development of geotourism objects to be more optimal, further research and infrastructure development is needed.